Vulnerability of Internally Displaced Persons in Urban Settings - World Bank; UNHCR (World Bank, Washington, DC, 2015)
Internal displacement, rapid growth of urban areas and proliferation of informal settlements are in the spotlight of public policy debate in Afghanistan at present. This pamphlet discusses characteristics, livelihood strategies and vulnerabilities of households living in informal settlements in three urban centers in Afghanistan. These findings summarize the analysis from a joint World Bank-UNHCR ‘research study on IDPs in urban settings’, which illustrates the complexities of displacement and of urban informal settlement growth. Motivated by an existing knowledge gap on these issues, the analysis provides a starting point for discussion among actors directly or indirectly involved with management of problems related to displacement and urban informal settlements, including departments in the Government of Afghanistan, international institutions and stakeholders from civil society. The study documents the significance of displacement as a factor underlying vulnerabilities observed in informal settlements, and identifies IDPs as an extremely deprived segment of the population, even in comparison to the profile of urban poverty in the recent national risk and vulnerability assessment.